A lottery on the first day of classes! An innovative structured steps assignment on a partially randomly selected topic. (January 2016) - Helmy, Heba E.
Abstract: In this paper we present an innovative in-depth writing assignment with structured steps in an undergraduate economic development course, where we bring two developing countries, randomly selected and represented by two students in class to write about, and later discuss, a certain development problem existing in the two countries, and to prove which country was more successful in overcoming its problem. The assignment started with its most exciting part – the lottery – which was used to assign countries for the students. The guideline, which comprised a detailed outline, important websites and how to use them, and a detailed rubric, provided students with the necessary answers to their inquiries. The feedback on the first part of the projects indicated not only the depth and width required but the degree of accuracy as well. The results were magnificent compared to traditional projects where students were only required to write on a topic of their choice with no accompanying clarifying material on the amount of depth and width required and with no feedback.